Assessing the Knowledge, Attitude, and Practice of Households in Darmian City with Regard to Municipal Solid Waste Management - Sahlabadi, Fatemeh; Moodi, Mitra; Sadani, Mohsen; Gerayllo, Sakineh; Mahmoodiyan, Ahmah; Pour, Hasan Mehran (International journal of environmental health engineering, 2024)
Abstract Aim: The purpose of this study was to investigate the knowledge, attitude, and practice of households living in Darmian city, South Khorasan, Iran, with regard to municipal solid waste (MSW) management. Methods: The quota sampling method was used based on Darmian city zoning. The questionnaire was included questions about knowledge, attitude, and practice in the MSW management domain. Data were analyzed by SPSS version 18 (SPSS Inc, Chicago) using descriptive statistics and appropriate nonparametric statistical tests. Results: The findings showed that the mean score of knowledge was 8.53 ± 2.46, of attitude was 16.60 ± 2.70, and of practice was 3.02 ± 1.10. It was found that the implementation of management plans could improve health and environmental aspects. Conclusion: According to the findings, the scores of knowledge and practice were higher among urban residents than rural ones. Therefore, proper planning for improving the cultural level of rural residents in this regard should be considered. To increase participation in waste separation and recycling practices, educational campaigns and mass media can be the used as one of the effective educational strategies.